Analysis of Hate Speech in the Perspective of Changes to the Electronic Information and Transaction Law - Hidayat, Defril; Firmanda, Hengki; Wafi, Mahmud Hibatul (Universitas Lampung, 2024)
This study aimed to assess the effectiveness of hate speech rules concerning changes in electronic transaction information policies. It further used normative legal study which included the process of identifying legal rules, principles, and doctrines to address the constitutional issues. The results showed that the amendments from the 2008 ITE Law to the 2016 ITE Law did not adequately the basic problems. Furthermore, certain forms of hate speech rules were observed in the ITE Law, particularly in Article 27 paragraph (3) and Article 28 paragraph (2). These rules were unclear benchmarks used in assessing social media posts as hate speech, defamation, or criticism and opinion from an individual about a problem. Therefore, making improvements through legal reform was essential to ITE Law, specifically Article 27 paragraph (3) and Article 28 paragraph (2). The amendments were necessary to develop good legal certainty for the community. The government should further make legal comparisons with other countries to identify the best regulatory framework for the community.